Rin Tin Tin : the life and the legend - Orlean, Susan (Simon & Schuster, 2011)
Allegedly found in the ruins of a bombed-out dog kennel in France during World War I, then brought to Los Angeles by Lee Duncan, the soldier who found and trained him, by 1927 Rin Tin Tin had become Hollywood's number one box-office star. Susan Orlean's book--about the dog and the legend--is a poignant exploration of the enduring bond between humans and animals. It is also a richly textured history of twentieth-century entertainment and entrepreneurship. It spans ninety years and explores everything from the shift in status of dogs from working farmhands to beloved family members, from the birth of obedience training to the evolution of dog breeding, from the rise of Hollywood to the past and present of dogs in war.--From publisher description.